Performance Analysis of 20 Gb/s QPSK Modulated Dual Polarization Coherent Optical OFDM Systems - Güner, Ahmet (Fırat University, 2017)
In this study, 20 Gb/s Dual Polarization Coherent Optical Orthogonal Frequency Division Multiplexing (DP-CO-OFDM) system is studied to obtain the relation between the Bit Error Rate (BER) and launch power for different transmission length and polarization mode dispersion (PMD) coefficient. DP-CO-OFDM system is simulated by designing a Monte Carlo simulation. In this simulation, the effects of chromatic dispersion, launch power and PMD coefficient on received signals are demonstrated with constellation diagrams and results are given in form of BER-Launch Power variations.